The Application of Amphibious Structures And Iot-Based Mitigation Systems: Empowering Coastal Communities To Cope With The Threat of Storm Surges On The East Coast North Sumatra Project Location: Belawan Sub-District, Medan Belawan District, Medan City, N - Bhakti Alamsyah; Ertina Sabarita Barus; Delima Sitanggang; Siti Aisyah; Evta Indra; Saut Parsaoran Tamba; Palma Juanda; Mohammad Irfan Fahmi; Yonata Laia; Hartantti Tammanah Lubis (International Journal Of Community Service, 2026)
The phenomenon of tidal flooding has become a recurring threat to coastal communities in Belawan Sub-district, Medan City, which forms part of the East Coast of North Sumatra—an area experiencing land subsidence and rising sea levels due to climate change. These conditions have led to damage to settlements, disruption to fishermen’s economic activities, and a decline in the environmental health of coastal communities. This community service initiative aims to empower the Belawan community through the implementation of two main approaches: amphibious construction as an adaptive architectural solution enabling floating dwellings to adjust to water level fluctuations; and an Internet of Things (IoT)-based mitigation system comprising water level monitoring sensors and an early warning system linked to a smartphone application. The implementation methods included a socialisation and vulnerability assessment phase, technical training on prototype-scale amphibious construction, installation of IoT devices, community mentoring, and an evaluation of the programme’s sustainability. The results of the activities demonstrate an increased understanding amongst the community of adaptive technologies based on local wisdom and appropriate technology, the construction of one prototype amphibious foundation unit at the home of an affected resident, and the functioning of a real-time tidal flood early warning system. It is hoped that this initiative will serve as a replicable model for the empowerment of coastal communities facing the threat of tidal flooding in other coastal areas of North Sumatra.